The effect of surface nucleation modulation on the mechanical and biocompatibility of metal-polymer biomaterials - Ye, Zhenhong; Zhang, Le; Liu, Taiwei; Xuan, Weicheng; He, Xiaodong; Hou, Changhao; Han, Donglin; Yu, Binbin; Shi, Junye; Kang, Jie; Chen, Jiangping (Frontiers in Bioengineering and Biotechnology, 2023)
The deployment of hernia repair patches in laparoscopic procedures is gradually increasing. In this technology, however, understanding the new phases of titanium from the parent phase on polymer substrates is essential to control the microstructural transition and material properties. It remains a challenging area of condensed matter physics to predict the kinetic and thermodynamic properties of metals on polymer substrates from the molecular scale due to the lack of understanding of the properties of the metal-polymer interface. However, this paper revealed the mechanism of nucleation on polymer substrates and proposed for the first record a time-dependent regulatory mechanism for the polymer-titanium interface. The interconnection between polymer surface chain entanglement, nucleation and growth patterns, crystal structure and surface roughness were effectively unified. The secondary regulation of mechanical properties was accomplished simultaneously to satisfy the requirement of biocompatibility. Titaniumized polypropylene patches prepared by time-dependent magnetron sputtering technology demonstrated excellent interfacial mechanical properties and biocompatibility. In addition, modulation by low-temperature plasma metal deposition opened a new pathway for biomaterials. This paper provides a solid theoretical basis for the research of titanium nanofilms on medical polypropylene substrates and the medical industry of implantable biomaterials, which will be of great value in the future.